Knowledge spillovers and diffusion of innovations as a driving force of economic development on the example of labor migration of researchers - L. S. Spankulova; A. R. Kerimbayev; E. Nuruly; D. R. Korgasbekov; Z. A. Lakhbaeva (Экономика: стратегия и практика, 2020)
The micro-and macro-aspects of interpretation of the diffusion nature of innovations spread, knowledge spillovers of between regions, on the example of labor migration of researchers are considered. The review of existing literature on the research issues is given, which contains the main ideas and results of research works, refracted into known facts. Three research approaches to studying knowledge spillovers are identified: studying cross-country trade flows, multidimensional analysis of patent data, and research of the placement of innovative companies based on their proximity to work places of highly-skilled specialists. The possible ways to strengthen competitiveness of regions by borrowing innovations are analyzed. The paper contains wording of the concept of “diffusion of innovations”, “knowledge spillovers”, as well as illustrations of the identified theoretical positions and examples of their practical manifestations. In addition, the paper notes that the professional mobility of scientists and highly-skilled specialists are the most obvious policy directions that contribute to knowledge spillovers and diffusion of innovations, since a high level of mobility of scientists contributes to rapid dissemination of research results. Moreover, migration process of researchers is associated with the new technologies transfer, because new knowledge creation is not a one-time event and is not implemented alone. The mobility of researchers has become a global phenomenon and is mainly due to economic factors.